Stability analysis of unsteady flow and heat transfer of rear stagnation point in hybrid nanofluids with thermal radiation and magnetic impact - Nurul Amira, Zainal; Iskandar, Waini; Najiyah Safwa, Khashi’ie; Khairum, Hamzah; Sayed Kushairi, Sayed Nordin; Abdul Rahman, Mohd Kasim; Roslinda, Mohd Nazar; Pop, Ioan Mihai (Semarak Ilmu Publishing, 2023)
In this study, the stability analysis is conducted in order to observe the reliability of the generated solutions. The influence of several parameters is taken into consideration including magnetic parameter, radiation parameter, and heat transfer. The well-known heat transfer fluid that is Al2O3-Cu/H2O hybrid nanofluid past a rear stagnation point is implied. The similarity equations are achieved after implying suitable similarity transformation which then needed to be solved numerically using bcp4c, embedded in MATLAB software. Dual solutions are observed along the investigation within specified values of involved parameters. It is important to note that verification results show excellent concordance with pre-existing reports.